Tongue bite in a patient with tracheostomy after prone position -A case report - Chae, Yun-Jeong; Kim, Jong-Yeop; Yoo, Ji-Young; Choi, Yi-Hwa; Park, Kwan-Sik (Korean journal of anesthesiology, 2011)
A 22-year-old man underwent an operation for posterolateral fusion of the lumbar spine at L3-5. He was ventilated via a tracheostomy site in a prone position for 210 minutes. Ventilator function and eyeballs were checked periodically. After changing his position to supine for the wake-up test, it was noticed that his tongue was self-inflicted and looked to be cut unless immediate decompression was applied. After several manual attempts to open the mouth failed, anesthesia depth was deepened with thiopental sodium and neuromuscular blocker to decompress and reposition the tongue into the intraoral cavity. Minimal teeth marks and scarring remained after seven months without any complications.